DEVELOPING A COMPASSIONATE SCHOOL CURRICULUM: A REVIEW OF LOVE-CENTERED CHARACTER EDUCATION - Rafika Nisa; Dwi Meutia Hasni; Fatma Gustina (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This research aims to analyze the concepts, implementation strategies, benefits, and challenges of developing a compassion-based school curriculum as an integrative approach in character education. The research uses a literature review method, examining scientific articles published in 2021–2026 obtained from Scopus, Web of Science, ERIC, ScienceDirect, SpringerLink, and Google Scholar. Literature was selected based on its relationship with character education, empathy, compassion, responsibility, social-emotional learning, caring pedagogy, and school culture. Data were analyzed using thematic content analysis, with stages including coding, theme grouping, comparison of findings, and conceptual synthesis. The results of the study show that a compassion-based curriculum needs to be built through the integration of three main dimensions, namely empathy as the ability to understand the experiences and perspectives of others, compassion as motivation to respond to difficulties prosocially, and responsibility as a commitment to act ethically and consider the consequences of actions. These three dimensions need to be applied through learning objectives, cross-subject materials, teacher examples, collaborative and reflective learning, authentic assessments, restorative practices, and a safe and inclusive school culture. The novelty of the study lies in the formulation of a conceptual architecture that integrates the goals, content, pedagogy, assessment, and culture of the school into a holistic, applied, and inclusive character education framework. Its implementation has the potential to improve social-emotional competence, prosocial behavior, sense of belonging to school, welfare, and student learning engagement. However, its implementation still faces limitations, including teacher training challenges, program fragmentation, variations across cultural contexts, uneven institutional support, and difficulties in measuring character development. This study emphasizes that a compassion-based curriculum must be developed systematically, contextually, and sustainably to cultivate students who excel academically as well as who are empathic, caring, fair, and responsible.